2011
DOI: 10.5152/akd.2011.001
|View full text |Cite
|
Sign up to set email alerts
|

Closure of patent ductus arteriosus with duct occluder device in adult patients: evaluation of the approaches to facilitate the procedure

Abstract: ÖZETAmaç: Erişkin hastaların patent duktus arteriyozus'ları (PDA) anatomik değişikler nedeniyle transkateter yöntemle kapatılması komplike olabilir. Bu çalışmanın amacı, erişkin hastaların Amplatzer duktus tıkayıcı (ADO) cihazı kullanarak transkateter yöntemle PDA kapatılmasında işlemi kolaylaştırıcı yaklaşımların değerlendirilmesidir. Yöntemler: Bu prospektif çalışmada yaşları 18 ile 56 arasında değişen orta-geniş PDA'lı ardışık 33 hasta ADO cihazı ile transkateter yöntemle kapatılma işlemine alındı. Patent d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
0
2

Year Published

2013
2013
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 25 publications
0
4
0
2
Order By: Relevance
“…One the most significant complication of percutaneously closure of PDA is device embolisation 241314151617. The reported rate of the major complication with ADO was 2.3% in a multi-centre registry 18…”
Section: Discussionmentioning
confidence: 99%
“…One the most significant complication of percutaneously closure of PDA is device embolisation 241314151617. The reported rate of the major complication with ADO was 2.3% in a multi-centre registry 18…”
Section: Discussionmentioning
confidence: 99%
“…However, this device can only be used for the closure of PDAs less than 6 mm in diameter [9]. In previous studies, it was reported that using oversized devices would be safe and could reduce the residual leakage, especially among patients with severe pulmonary hypertension [10, 11]. Paç et al .…”
Section: Discussionmentioning
confidence: 99%
“…Paç et al . have also recommended the use of larger devices in adult patients to reduce the risk of embolization to the pulmonary artery [11]. Thanopoulos et al .…”
Section: Discussionmentioning
confidence: 99%
“…ADO ile yapılmış çok sayıda çalışma mevcuttur. Çocuk ve erişkinleri kapsayan 439 vakalık bir seride ADO I cihazı ile başarılı kapatma oranı bir yıl sonunda %99.7 olarak bildirilmiştir.10 Ülkemizde de bu gelişmelere paralel olarak birçok merkezde PDA'ların perkütan yolla kapatılması başarılı bir şekilde gerçekleştirilmektedir [16][17][18][19][20][21]. Kaya ve ark.…”
Section: Discussionunclassified